Graphite negative electrode material and preparation method thereof, dry electrode, battery and electric equipment

By preparing a polymer cladding layer that conducts ions but does not conduct electrons on the graphite negative electrode material, the side reaction problem caused by the reaction of PTFE and lithium ions is solved, and the electrochemical performance of the battery is significantly improved.

CN119542390APending Publication Date: 2025-02-28GAC AION NEW ENERGY AUTOMOBILE CO LTD
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202411716398.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

When using polytetrafluoroethylene (PTFE) as the binder for the existing dry electrode, PTFE reacts with lithium ions on the negative electrode surface, resulting in side reactions, reducing the first discharge capacity, first effect and cycling performance of the battery.

Method used

Graphite negative electrode material is used, graphite is used as the core, and the shell is a polymer coating that conducts ions but not electrons. It is prepared by heat treatment to block electron tunneling and prevent side reactions between PTFE and lithium ions.

Benefits of technology

Effectively inhibit the side reaction between PTFE and lithium ions on the negative electrode surface, and improve the battery's first discharge capacity, first effect and cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542390A_ABST
    Figure CN119542390A_ABST
Patent Text Reader

Abstract

The invention provides a graphite negative electrode material and a preparation method thereof, a dry-method electrode, a battery and electric equipment, and belongs to the technical field of battery manufacturing. The graphite negative electrode material is of a core-shell structure, an inner core is graphite, a shell is a polymer coating layer, the polymer coating layer can conduct ions but cannot conduct electrons, and the graphite negative electrode material can effectively inhibit PTFE from generating side reaction with lithium ions on the surface of a negative electrode, so that the first discharge gram capacity, the first effect and the cycle performance of a corresponding battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery manufacturing technology, and in particular to a graphite negative electrode material and a preparation method thereof, a dry electrode, a battery and an electrical device. Background Art

[0002] Commercial lithium-ion battery pole pieces are usually prepared using wet slurry coating technology. This pole piece preparation method has the disadvantages of toxic solvents (such as N-methylpyrrolidone), large investment in solvent recovery, large coating oven footprint, and high energy consumption. At the same time, the surface density of the prepared pole piece is low.

[0003] Based on this, a dry electrode preparation technology has been designed. Specifically, the active material and the conductive agent are dry-mixed evenly by powder extrusion molding, and then the adhesive is added. After the adhesive is fiberized, it is rolled to form a self-supporting film. Finally, the self-supporting film is rolled and covered on the surface of the current collector to obtain a dry electrode. The dry electrode preparation technology does not require the use of solvents, eliminates the electrode drying and solvent recovery links, has a simpler process flow, and occupies a smaller area of ​​equipment. If mass production is carried out, lower electrode manufacturing costs can be achieved.

[0004] At present, dry electrodes usually use polytetrafluoroethylene (PTFE) as a binder because it can form a mesh-structured fiber under the action of external shear force, which is the key to the subsequent preparation of a self-supporting membrane. However, PTFE will react with lithium ions on the surface of the negative electrode to form lithium fluoride, which will weaken the bonding effect and reduce the capacity (single gram of PTFE will consume about 1070mAh of lithium, and the higher the PTFE content in the battery, the more lithium is consumed), thereby affecting the battery performance (such as but not limited to the first discharge gram capacity, first efficiency and cycle performance). Summary of the invention

[0005] The purpose of the present application is to provide a graphite negative electrode material and a preparation method thereof, a dry electrode, a battery and an electrical device. The graphite negative electrode material can effectively inhibit the side reaction of PTFE with lithium ions on the negative electrode surface, thereby improving the first discharge gram capacity, first efficiency and cycle performance of the corresponding battery.

[0006] The embodiment of the present application is implemented as follows:

[0007] In a first aspect, an embodiment of the present application provides a graphite negative electrode material, wherein the graphite negative electrode material is a core-shell structure, wherein the core is graphite and the shell is a polymer coating layer, and the polymer coating layer can conduct ions but not electrons.

[0008] In the above technical solution, graphite is used as the core, and then a polymer coating layer is arranged on its surface, wherein the polymer coating layer has the property of being able to conduct ions but not electrons. On the one hand, this property enables graphite to normally participate in the charge and discharge cycle of the battery to ensure the normal operation of the battery; on the other hand, it can block electron tunneling and prevent PTFE from being affected by the reduction potential of the graphite negative electrode, thereby effectively inhibiting the side reaction of PTFE with lithium ions on the negative electrode surface, thereby improving the first discharge capacity, first efficiency and cycle performance of the corresponding battery.

[0009] In some optional embodiments, the material of the polymer coating layer is selected from at least one of carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone, polymethyl methacrylate, polyvinyl chloride and polyvinylidene chloride.

[0010] In the above technical solution, the polymer coating layer of a specific material not only has the property of being able to conduct ions but not electrons, but also has good electrochemical reduction stability, which is more helpful to improve the first discharge gram capacity, first efficiency and cycle performance of the corresponding battery.

[0011] In some optional embodiments, the material of the polymer coating layer is selected from at least one of carboxymethyl cellulose, polyvinylidene fluoride and polymethyl methacrylate.

[0012] In the above technical solution, the polymer coating layer of specific material has more excellent electrochemical reduction stability, which can further improve the first discharge gram capacity, first efficiency and cycle performance of the corresponding battery.

[0013] In some optional embodiments, the mass ratio of graphite to polymer coating layer is (95-96.5): (0.5-2).

[0014] In the above technical scheme, the mass ratio of graphite and polymer coating is limited to a specific range so that the polymer coating has an appropriate thickness, thereby being able to better balance the properties of ion conductivity and electron blocking (if the coating is too thick, the ion conductivity is poor; if the coating is too thin, the electron blocking performance is poor).

[0015] In a second aspect, the present application provides a method for preparing a graphite negative electrode material as provided in the first aspect, comprising the following steps:

[0016] The coated polymer is added to a solvent and mixed to obtain a polymer solution; graphite is added to the polymer solution and mixed to obtain a mixed solution; the mixed solution is heat-treated until all the solvent in the mixed solution is volatilized to obtain a graphite negative electrode material.

[0017] In the above technical scheme, a graphite negative electrode material with a polymer coating layer on the surface can be prepared according to a specific process, wherein the polymer coating layer has the property of being able to conduct ions but not electrons, and can effectively inhibit the side reaction of PTFE with lithium ions on the negative electrode surface, thereby improving the first discharge capacity, first efficiency and cycle performance of the corresponding battery.

[0018] In some optional embodiments, the mass percentage of the coating polymer in the polymer solution is 1-5%.

[0019] In the above technical solution, the mass percentage of the coating polymer in the polymer solution is limited to a specific range so that the polymer solution has an appropriate concentration, which helps to improve the coating uniformity and prepare a polymer coating layer with good coating integrity and uniform thickness.

[0020] In a third aspect, an embodiment of the present application provides a dry electrode, comprising a current collector and an electrode film located on one side or both sides of the current collector, wherein the electrode film comprises a graphite negative electrode material, a conductive agent and polytetrafluoroethylene as provided in the embodiment of the first aspect.

[0021] In the above technical scheme, the electrode membrane in the dry electrode includes the graphite negative electrode material provided in the first aspect embodiment. The polymer coating layer on the surface of the graphite negative electrode material has the property of being able to conduct ions but not electrons, and can effectively inhibit the side reaction of PTFE with lithium ions on the negative electrode surface, thereby improving the first discharge capacity, first efficiency and cycle performance of the corresponding battery.

[0022] In some optional embodiments, the mass ratio of graphite negative electrode material in the electrode film is 96-98%, and / or the mass ratio of conductive agent to polytetrafluoroethylene is (1.5-2.5): (0.5-1.5).

[0023] In the above technical solution, the mass proportion of the graphite negative electrode material in the electrode film and the mass ratio of the conductive agent and polytetrafluoroethylene are respectively limited within specific ranges, so that the prepared electrode film has relatively excellent comprehensive electrical properties.

[0024] In some optional embodiments, the thickness of the single-layer electrode film is 50-150 μm.

[0025] In the above technical solution, the thickness of the single-layer electrode film is limited to a specific range so that it has a relatively ideal compaction density and surface density, thereby making the corresponding battery have a relatively ideal comprehensive electrical performance.

[0026] In some optional embodiments, the weight average molecular weight of polytetrafluoroethylene is 4×10 7 ~8×10 7 .

[0027] In the above technical solution, polytetrafluoroethylene with a specific weight average molecular weight is used, which has the advantages of good bonding effect and fiberization effect.

[0028] In some optional embodiments, the current collector is a carbon-coated copper foil, and the thickness of the current collector is 5 to 10 μm.

[0029] In the above technical solution, carbon-coated copper foil is used as the current collector, which is more conducive to the preparation of dry electrodes; in addition, the thickness of the current collector is further limited to a specific range so that it has a more suitable strength, so that it can better load and support the electrode film.

[0030] In a fourth aspect, an embodiment of the present application provides a battery, comprising a dry electrode provided in the embodiment of the third aspect.

[0031] In a fifth aspect, an embodiment of the present application provides an electrical device, comprising a battery as provided in the embodiment of the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 A schematic cross-sectional view of a graphite negative electrode material provided in an embodiment of the present application;

[0034] Figure 2 A process flow chart of a method for preparing a graphite negative electrode material provided in an embodiment of the present application.

[0035] Icon: 10-graphite negative electrode material; 100-core; 200-shell. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0037] It should be noted that “and / or” in this application, such as “Feature 1 and / or Feature 2”, refers to the three situations of “Feature 1” alone, “Feature 2” alone, or “Feature 1” plus “Feature 2”.

[0038] In addition, in the description of the present application, unless otherwise specified, the meaning of "multiple" in "one or more" refers to two or more; the range of "value a ~ value b" includes the two end values ​​"a" and "b", and the "unit" in "value a ~ value b + unit of measurement" represents the "unit of measurement" of both "value a" and "value b".

[0039] The following is a detailed description of the graphite negative electrode material and its preparation method, dry electrode, battery and electrical equipment in the embodiments of the present application.

[0040] See also Figure 1 In the first aspect, an embodiment of the present application provides a graphite negative electrode material 10, and the graphite negative electrode material 10 is a core-shell structure, wherein the core 100 is graphite, and the shell 200 is a polymer coating layer, and the polymer coating layer can conduct ions but not electrons.

[0041] In the present application, graphite is used as the core 100, and then a polymer coating layer is arranged on its surface, wherein the polymer coating layer has the property of being able to conduct ions but not electrons. On the one hand, this property enables graphite to normally participate in the charge and discharge cycle of the battery to ensure the normal operation of the battery; on the other hand, it can block electron tunneling and prevent PTFE from being affected by the reduction potential of the graphite negative electrode, thereby effectively inhibiting the side reaction of PTFE with lithium ions on the negative electrode surface, thereby improving the first discharge capacity, first efficiency and cycle performance of the corresponding battery.

[0042] It should be noted that the solution for coating and modifying graphite provided in the embodiment of the present application, compared with the solution for coating and modifying PTFE in the prior art, will not affect the bonding effect and subsequent fiberization effect of PTFE, so that the corresponding battery can have better comprehensive electrical performance.

[0043] As an example, the material of the polymer coating layer is selected from at least one of carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone, polymethyl methacrylate, polyvinyl chloride and polyvinylidene chloride.

[0044] In this embodiment, the polymer coating layer of a specific material has the property of being able to conduct ions but not electrons and also has good electrochemical reduction stability, thereby being more helpful in improving the first discharge capacity, first efficiency and cycle performance of the corresponding battery.

[0045] As an example, the material of the polymer coating layer is selected from at least one of carboxymethyl cellulose, polyvinylidene fluoride and polymethyl methacrylate.

[0046] In this embodiment, the polymer coating layer of a specific material has more excellent electrochemical reduction stability, and can further improve the first discharge gram capacity, first efficiency and cycle performance of the corresponding battery.

[0047] It should be noted that the ion-conducting but electron-non-conducting property of the polymer coating layer is closely related to its thickness. Based on this, the parameters related to the coating thickness can be defined.

[0048] As an example, the mass ratio of graphite to polymer coating is (95-96.5):(0.5-2), such as but not limited to any one of 95:2, 96:1 and 96.5:0.5 or a range between any two of the mass ratios.

[0049] In this embodiment, the mass ratio of graphite and polymer coating is limited to a specific range so that the polymer coating has an appropriate thickness, thereby being able to better balance the properties of ion conductivity and electron blocking (if the coating is too thick, the ion conductivity is poor; if the coating is too thin, the electron blocking performance is poor).

[0050] In a second aspect, the present application provides a method for preparing a graphite negative electrode material as provided in the first aspect, comprising the following steps:

[0051] The coated polymer is added to a solvent and mixed to obtain a polymer solution; graphite is added to the polymer solution and mixed to obtain a mixed solution; the mixed solution is heat-treated until all the solvent in the mixed solution is volatilized to obtain a graphite negative electrode material.

[0052] In the present application, a graphite negative electrode material with a polymer coating layer on the surface can be prepared according to a specific process, wherein the polymer coating layer has the property of being able to conduct ions but not electrons, and can effectively inhibit the side reaction of PTFE with lithium ions on the negative electrode surface, thereby improving the first discharge capacity, first efficiency and cycle performance of the corresponding battery.

[0053] It should be noted that different types of coating polymers usually have different solubility, so the type of solvent needs to be adaptively adjusted according to the type of corresponding coating polymer.

[0054] As an example, when the coating polymer is carboxymethyl cellulose, the corresponding solvent is water.

[0055] As an example, when the coating polymer is at least one of polyvinylidene fluoride, polyvinyl pyrrolidone, polymethyl methacrylate, polyvinyl chloride and polyvinylidene chloride, the corresponding solvent is a low boiling point alcohol solution, such as ethanol.

[0056] As an example, the mass percentage of the coating polymer in the polymer solution is 1-5%, for example but not limited to any one of 1%, 2%, 3%, 4% and 5% or a range between any two of them.

[0057] In this embodiment, the mass percentage of the coating polymer in the polymer solution is limited to a specific range so that the polymer solution has a suitable concentration, which helps to improve the coating uniformity and prepare a polymer coating layer with good coating integrity and uniform thickness.

[0058] It should be noted that since the mass of graphite and coated polymer does not change before and after coating, the dosage standards of graphite and coated polymer in the preparation process can refer to the mass proportion of each component in the product in the embodiment of the first aspect.

[0059] It should be noted that, in the step of heat-treating the mixed solution, the specific treatment temperature can be adaptively adjusted according to the type of solvent used, as long as the solvent can be completely volatilized.

[0060] It should be noted that any process or step not specifically described or limited in the preparation of the graphite negative electrode material may be arranged according to conventional selection in the art.

[0061] As an example, in the step of adding graphite to the polymer solution and mixing, the stirring speed is 100 to 1000 rpm, for example but not limited to, the stirring speed is any one of 100 rpm, 200 rpm, 400 rpm, 600 rpm, 800 rpm and 1000 rpm or a range between any two of them.

[0062] As an example, the process flow chart of the preparation method of the graphite negative electrode material is exemplified by referring to Figure 2 .

[0063] In a third aspect, an embodiment of the present application provides a dry electrode, comprising a current collector and an electrode film located on one side or both sides of the current collector, wherein the electrode film comprises a graphite negative electrode material, a conductive agent and polytetrafluoroethylene as provided in the embodiment of the first aspect.

[0064] In the present application, the electrode membrane in the dry electrode includes a graphite negative electrode material as provided in the first aspect embodiment. The polymer coating layer on the surface of the graphite negative electrode material has the property of being able to conduct ions but not electrons, and can effectively inhibit the side reaction of PTFE with lithium ions on the negative electrode surface, thereby improving the first discharge capacity, first efficiency and cycle performance of the corresponding battery.

[0065] As an example, the mass proportion of graphite negative electrode material in the electrode film is 96-98%, for example but not limited to the mass proportion of 96%, 96.5%, 97%, 97.5% and 98% or any point value or a range value between any two of them; and / or, the mass ratio of the conductive agent and polytetrafluoroethylene is (1.5-2.5): (0.5-1.5), for example but not limited to the mass ratio of 1.5:1.5, 2:1 and 2.5:0.5 or any point value or a range value between any two of them.

[0066] In this embodiment, the mass proportion of the graphite negative electrode material in the electrode film and the mass ratio of the conductive agent to polytetrafluoroethylene are respectively limited within specific ranges, so that the prepared electrode film has relatively excellent comprehensive electrical properties.

[0067] As an example, the thickness of the single-layer electrode film is 50-150 μm, for example but not limited to any one of 50 μm, 80 μm, 100 μm, 120 μm and 150 μm or a range between any two of the thicknesses.

[0068] In this embodiment, the thickness of the single-layer electrode film is limited to a specific range so that it has a relatively ideal compaction density and surface density, thereby making the corresponding battery have a relatively ideal comprehensive electrical performance.

[0069] As an example, the weight average molecular weight of polytetrafluoroethylene is 4×10 7 ~8×10 7 , for example but not limited to a weight average molecular weight of 4×10 7 , 5×10 7 , 6×10 7 ,7×10 7 and 8×10 7 Any point value in or any range of values ​​between them.

[0070] In this embodiment, polytetrafluoroethylene with a specific weight average molecular weight is used, which has the advantages of good bonding effect and fiberization effect.

[0071] As an example, the current collector is a carbon-coated copper foil, and the thickness of the current collector is 5 to 10 μm, for example but not limited to any one of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm and 10 μm or a range between any two of the thicknesses.

[0072] In this embodiment, carbon-coated copper foil is used as the current collector, which is more conducive to the preparation of dry electrodes; in addition, the thickness of the current collector is further limited to a specific range so that it has a more suitable strength, so that it can better load and support the electrode film.

[0073] It should be noted that any structure not specifically described or limited in the dry electrode may be configured according to conventional selections in the art.

[0074] As an example, the conductive agent is selected from at least one of carbon nanotubes and conductive carbon black.

[0075] It should be noted that the preparation method of the dry electrode can be set according to the conventional selection in the art.

[0076] As an example, the preparation method of a dry electrode includes the following steps: adding a graphite negative electrode material, a conductive agent and PTFE in a mass ratio into a powder device for dry mixing to obtain a uniformly dispersed composite material; adding the composite material into an air flow mill for further dispersion of the composite material and fiberization of the binder; rolling the fiberized material through a roller press to obtain a self-supporting electrode film, and finally rolling the self-supporting electrode film together with the foil material to roll and compound the two together to obtain a dry electrode.

[0077] As an example, in the process of rolling the fiberized material through a roller press to obtain a self-supporting electrode film, the processing temperature of the roller press is 50-150°C, for example but not limited to the processing temperature of any point value among 50°C, 80°C, 100°C, 120°C and 150°C or a range value between any two of them.

[0078] In a fourth aspect, an embodiment of the present application provides a battery, comprising a dry electrode provided in the embodiment of the third aspect.

[0079] It should be noted that any structural or functional unit not specifically described in the battery may be configured according to conventional selections in the art.

[0080] In a fifth aspect, an embodiment of the present application provides an electrical device, comprising a battery as provided in the embodiment of the fourth aspect.

[0081] It should be noted that there is no limitation on the types of electrical equipment, such as mobile phones, portable devices, laptops, electric vehicles, electric cars, ships, spacecraft, electric toys, energy storage devices and electric tools.

[0082] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0083] Example 1

[0084] The present invention provides a method for preparing a dry electrode, comprising the following steps:

[0085] (1) Preparation of graphite negative electrode materials

[0086] The coated polymer (carboxymethyl cellulose) is added to water and stirred to obtain a polymer solution; wherein the mass percentage of carboxymethyl cellulose in the polymer solution is 3%. Graphite is added to the polymer solution and stirred at room temperature (25°C) for 3 hours to obtain a mixed solution; wherein the mass ratio of graphite to the coated polymer is 96:1, and the stirring speed is 500rpm. The mixed solution is heat treated at 100°C until all the water in the mixed solution is volatilized to obtain a graphite negative electrode material.

[0087] (2) Dry electrode preparation

[0088] The graphite negative electrode material, the conductive agent and PTFE were added into the powder equipment in a mass ratio of 97:1.5:1.5 for dry mixing to obtain a uniformly dispersed composite material; wherein the conductive agent was carbon nanotubes, and the weight average molecular weight of PTFE was 6×10 7 The composite material is added into the air flow mill to further disperse the composite material and fiberize the binder; the fiberized material is rolled by a roller press (processing temperature is 100°C) to obtain a self-supporting electrode film with a thickness of 100 μm, and finally the self-supporting electrode film is rolled together with a carbon-coated copper foil (thickness is 10 μm) to roll the self-supporting electrode film and the single-sided carbon-coated copper foil together to obtain a dry electrode.

[0089] Example 2

[0090] The embodiment of the present application provides a method for preparing a dry electrode, which differs from Embodiment 1 only in that in step (1), the mass ratio of graphite to coating polymer is 95:2.

[0091] Example 3

[0092] The embodiment of the present application provides a method for preparing a dry electrode, which differs from Embodiment 1 only in that: in step (1), the mass ratio of graphite to coating polymer is 96.5:0.5.

[0093] Example 4

[0094] The embodiment of the present application provides a method for preparing a dry electrode, which differs from Embodiment 1 only in that in step (1), the mass ratio of graphite to coating polymer is 94:3.

[0095] Example 5

[0096] The embodiment of the present application provides a method for preparing a dry electrode, which differs from Embodiment 1 only in that: in step (1), the mass ratio of graphite to coating polymer is 96.8:0.2.

[0097] Example 6

[0098] The present embodiment provides a method for preparing a dry electrode, which differs from the embodiment 1 only in that: in step (1), a coating polymer (polyvinyl pyrrolidone) is added to ethanol and stirred to obtain a polymer solution; wherein the mass percentage of polyvinyl pyrrolidone in the polymer solution is 3%. Graphite is added to the polymer solution and stirred at room temperature (25°C) for 3 hours to obtain a mixed solution; wherein the mass ratio of graphite to the coating polymer is 96:1, and the stirring speed is 500 rpm. The mixed solution is heat treated at 80°C until all the ethanol in the mixed solution is volatilized to obtain a graphite negative electrode material.

[0099] Comparative Example 1

[0100] The comparative example of the present application provides a method for preparing a dry electrode, comprising the following steps:

[0101] Graphite (uncoated), conductive agent and PTFE were added into a powder equipment in a mass ratio of 97:1.5:1.5 for dry mixing to obtain a uniformly dispersed composite material; wherein the conductive agent was carbon nanotubes, and the weight average molecular weight of PTFE was 6×10 7 The composite material is added into the air flow mill to further disperse the composite material and fiberize the binder; the fiberized material is rolled by a roller press (processing temperature is 100°C) to obtain a self-supporting electrode film with a thickness of 100 μm, and finally the self-supporting electrode film is rolled together with a carbon-coated copper foil (thickness is 10 μm) to roll the self-supporting electrode film and the single-sided carbon-coated copper foil together to obtain a dry electrode.

[0102] Comparative Example 1

[0103] The comparative example of the present application adopts conventional wet slurry coating technology to prepare the electrode.

[0104] Test example

[0105] Electrical performance test of electrodes

[0106] Test method:

[0107] The dry electrodes (i.e., positive electrodes) prepared in Examples 1 to 6 and Comparative Example 1 and Reference Example 1 were assembled into lithium secondary ion batteries and numbered accordingly, and then the first discharge gram capacity, first efficiency, and cycle performance of each lithium secondary battery were tested.

[0108] The lithium secondary battery is assembled as follows:

[0109] S1 is mixed with LiNi in a mass ratio of 96.8:2.0:1.2 0.8 Co 0.1 Mn 0.1O2 (positive electrode active material), conductive carbon black (conductive agent) and polyvinylidene fluoride (binder) are dispersed in N-methyl-2-pyrrolidone to obtain positive electrode slurry; then, the positive electrode slurry is evenly coated on both sides of the aluminum foil; then, after drying, calendering and vacuum drying in sequence, an aluminum lead wire is welded with an ultrasonic welder to obtain a positive electrode sheet with a thickness of 125μm.

[0110] S2 stacks the prepared dry electrode (i.e., the negative electrode sheet), separator (PE-coated ceramic separator, thickness of 20 μm) and positive electrode sheet in order and winds them to obtain a bare battery cell. Then, the bare battery cell is injected with liquid (wherein the electrolyte composition is 1 mol / L LiPF6 / EC+DMC+EMC+FEC (volume ratio of 1:1:1:0.1)), packaged, allowed to stand, formed, shaped and capacity tested to obtain a lithium secondary battery.

[0111] The test steps for the first discharge capacity are as follows:

[0112] At 25°C, the battery is charged to 4.25V at a constant current of 0.33C, then charged at a constant voltage until the current is less than or equal to 0.05C, then left to stand for 5 minutes, and then discharged to 2.8V at a constant current of 0.33C, then left to stand for 5 minutes. This is a charge and discharge cycle, and the discharge capacity is recorded as the discharge capacity of the first cycle of the battery. Discharge gram capacity = discharge capacity / mass of active material.

[0113] The first-effect test steps are as follows:

[0114] At 25°C, the battery is charged to 4.25V at a constant current of 0.33C, then charged at a constant voltage until the current is less than or equal to 0.05C, then left to stand for 5 minutes, and then discharged to 2.8V at a constant current of 0.33C, then left to stand for 5 minutes. This is a charge and discharge cycle, and the charge and discharge capacity of this time is recorded as the first charge and discharge capacity. First efficiency (first coulomb efficiency) = first discharge capacity / first charge capacity × 100%.

[0115] The test steps for cycle performance are as follows:

[0116] At 25°C, the battery is charged to 4.25V at 1C constant current, then charged at constant voltage until the current is less than or equal to 0.05C, then left to stand for 5 minutes, and then discharged to 2.8V at 1C constant current, then left to stand for 5 minutes. This is a charge and discharge cycle. The battery cell is tested for multiple cycles of charge and discharge in the above manner, and the charge and discharge capacity of the 500th cycle is detected, and the capacity retention rate of the battery cell after the cycle is calculated by the following formula. Capacity retention rate of the battery after 500 cycles (%) = [discharge capacity of the 500th cycle / discharge capacity of the 1st cycle] × 100%.

[0117] Table 1 Electrical performance statistics

[0118]

[0119]

[0120] Referring to Table 1, it can be seen from the test results of Example 1, Comparative Example 1 and Reference Example 1 that the graphite negative electrode material provided in the embodiment of the present application has a polymer coating layer on the surface that conducts ions but does not conduct electrons. Compared with the existing graphite that has not been coated and modified, the battery corresponding to the former can effectively inhibit the side reaction of PTFE with lithium ions on the negative electrode surface, so that the corresponding battery has relatively excellent first discharge capacity per gram, first efficiency and cycle performance, and many electrical properties are comparable to those of the battery prepared by wet slurry coating technology.

[0121] It can be seen from the test results of Examples 1 to 3 and Examples 4 to 5 that in the process of preparing graphite negative electrode materials, the mass ratio of graphite and coating polymer is limited within a specific range so that the coating layer has an appropriate thickness. Compared with the mass ratio of graphite and coating polymer not being within the limited range, the polymer coating layer formed by the former can better balance the properties of ion conduction and electron blocking, so that the corresponding battery has relatively excellent first discharge capacity per gram, first efficiency and cycle performance.

[0122] It can be seen from the test results of Example 1 and Example 6 that by using a polymer with better electrochemical stability as a coating material, the prepared battery has better first discharge capacity per gram, first efficiency and cycle performance.

[0123] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

Claims

1. A graphite negative electrode material, characterized in that: The graphite negative electrode material is a core-shell structure, wherein the core is graphite and the shell is a polymer coating layer, and the polymer coating layer can conduct ions but cannot conduct electrons.

2. The graphite negative electrode material according to claim 1, characterized in that The material of the polymer coating layer is selected from at least one of carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone, polymethyl methacrylate, polyvinyl chloride and polyvinylidene chloride.

3. The graphite negative electrode material according to claim 2, characterized in that: The material of the polymer coating layer is selected from at least one of the carboxymethyl cellulose, the polyvinylidene fluoride and the polymethyl methacrylate.

4. The graphite negative electrode material according to any one of claims 1 to 3, characterized in that The mass ratio of the graphite to the polymer coating layer is (95-96.5): (0.5-2).

5. A method for preparing a graphite negative electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: adding the coating polymer into a solvent and mixing to obtain a polymer solution; adding graphite to the polymer solution and mixing to obtain a mixed solution; The mixed solution is heat treated until the solvent in the mixed solution is completely volatilized to obtain the graphite negative electrode material.

6. The method for preparing a graphite negative electrode material according to claim 5, characterized in that: The mass percentage of the coating polymer in the polymer solution is 1-5%.

7. A dry electrode, characterized in that: The invention comprises a current collector and an electrode film located on one side or both sides of the current collector, wherein the electrode film comprises the graphite negative electrode material according to any one of claims 1 to 5, a conductive agent and polytetrafluoroethylene.

8. The dry electrode according to claim 7, characterized in that: The mass ratio of the graphite negative electrode material in the electrode film is 96-98%, and / or the mass ratio of the conductive agent to the polytetrafluoroethylene is (1.5-2.5): (0.5-1.5).

9. The dry electrode according to claim 7, characterized in that: The thickness of a single-layer electrode film is 50 to 150 μm.

10. The dry electrode according to claim 7, characterized in that: The weight average molecular weight of the polytetrafluoroethylene is 4×10 7 ~8×10 7 .

11. The dry electrode according to claim 7, characterized in that: The current collector is a carbon-coated copper foil, and the thickness of the current collector is 5 to 10 μm.

12. A battery, characterized in that: It comprises the dry electrode as claimed in any one of claims 7 to 11.

13. An electrical equipment, characterized in that: Comprising the battery of claim 12.

Citation Information

Cited By

  • Negative electrode material and preparation method and application thereof

    CN120600782A

  • Negative electrode material for inhibiting decomposition of PTFE (Polytetrafluoroethylene) and dry-method electrode preparation method of negative electrode material

    CN121394368A

  • Negative electrode coating agent for dry-method electrode, negative electrode powder, preparation method of negative electrode powder, dry-method negative electrode plate, preparation process of dry-method negative electrode plate and battery

    CN121546063A

  • Dry-method negative electrode material and preparation method thereof, dry-method negative electrode and lithium ion battery

    CN122202275A

  • Negative electrode mixture, dry negative electrode sheet, and preparation method therefor and use thereof

    WO2025261011A1